Green complexation for heavy metals removal from wastewater by Keggin-polyoxometalates enhanced ultrafiltration - Kahloul, Malak (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
The presence of heavy metals in wastewater has become a serious issue and a global concern for the environment and public health with rapid progress of modern textile industry. To minimize the health risks of heavy metals their complexation to a chelating agent constitute a promising process using membrane separation. We highlight for the first time the use of Keggin type-polyoxometalates (PW12) as complexing agent to eliminate heavy metals from synthetic textile wastewater. Indeed, filtration experiments were performed through the ultrafiltration organic regenerated cellulose membrane (3KDa). Effects of pressure (1-2.5 bar), PW12 concentration (10-50 mg·L-1), salt concentration (10-4-2 M) and pH value (2-12) on cadmium (Cd) and copper (Cu) removal were regularly explored. Experimental data showed that the addition of PW12 improves metal removal efficiency (up to 90%). The addition of NaCl salt significantly decreases the metals retention to 42%. The retention drop is probably due to the competition between Na+ and metals on complexation same negative sites of the PW12 and to the electric double-layer compressing. 24 full factorial design has been used to evaluate the most influencing parameters. The results obtained revealed that the maximum metal retention was 99% for both Cd and Cu